The Urgency of Learning the History of Islamic Culture: Digital Literation Based - Yuyun Yumiarty; Bakti Komalasari; Muhammad Kristiawan (AJIS: Academic Journal of Islamic Studies, 2021)
The aim of this research is to explain the significance of digital literacy-based learning in the study of SKI at Madrasah Ibtidaiyah. In fact, few teachers have introduced digital literacy-based learning in the classroom. This is due to teachers' lack of understanding of how to use digital technology. This thesis employs qualitative descriptive analysis techniques in conjunction with field research. Techniques for gathering data included observation, interviews, and documentation. Descriptive analysis methods were used to analyze the data. Furthermore, comparing, checking the data's validity, and decrypting the data are all tasks that must be completed. The study's findings show that SKI's digital literacy-based learning is divided into four stages: (1) learning preparation, which includes deciding digital content based on the syllabus and lesson plans that will be provided to students; (2) digital material selection, which includes choosing digital files that will be shown during learning, such as images, movies, animated videos, or songs by examining whether or not the digital file is authorized. The learning material presented becomes more relevant and students become more engaged in learning as a result of digital literacy. This study serves as a resource for teachers interested in implementing digital literacy-based SKI learning, especially at Madrasah Ibtidaiyah